2013
DOI: 10.1590/brag.2013.053
|View full text |Cite
|
Sign up to set email alerts
|

Trocas gasosas e estresse oxidativo em plantas de algodoeiro supridas com silício e infectadas por Ramularia areola

Abstract: ResumoConsiderando o efeito positivo do silício (Si) na melhoria do desempenho fisiológico de várias espécies de plantas quando infectadas por patógenos, este trabalho teve como meta investigar o efeito desse elemento na capacidade fotossintética e no metabolismo antioxidativo de plantas dos cultivares de algodoeiro NuOpal e BRS Buriti, supridas ou não com Si, durante o processo infeccioso de Ramularia areola. A infecção por R. areola afetou negativamente a taxa líquida de fixação do CO 2 (A), a condutância es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…Silicon acts in osmotic regulation by increasing the K + absorption, the osmotic pressure regulating ion, responsible for stomatal opening and closing (Mahdieh et al, 2015;Verma et al, 2020). This fact can be proven from results with Gossypium hirsutum L., which when supplied with Si, increased A and gs (Curvêlo et al, 2013). The A, E, iCE and iWUE and POD activity increased in Z. mays plants whose seeds were soaked with in Thiabendazol ® .…”
Section: Discussionmentioning
confidence: 93%
“…Silicon acts in osmotic regulation by increasing the K + absorption, the osmotic pressure regulating ion, responsible for stomatal opening and closing (Mahdieh et al, 2015;Verma et al, 2020). This fact can be proven from results with Gossypium hirsutum L., which when supplied with Si, increased A and gs (Curvêlo et al, 2013). The A, E, iCE and iWUE and POD activity increased in Z. mays plants whose seeds were soaked with in Thiabendazol ® .…”
Section: Discussionmentioning
confidence: 93%
“…Lewis et al (2011), studying variations among Eucalyptus species, found a similar A value to this study (13 µmol m 2 s −1 ). Another benefit of Si application is the increase in the chlorophyll concentration of leaves (Epstein, 2001;Curvêlo et al, 2013). With this, we can presume that the 0.75 mmol Si L −1 rate provided a trend of higher photosynthetic rates, due to better leaf architecture such as higher leaf angles and chlorophyll concentration.…”
Section: Discussionmentioning
confidence: 97%
“…: insetos-praga, patógenos, herbívoros etc.) (Curvêlo et al, 2013;Moreno et al, 2021) e abióticos (ex. : temperatura, água, luminosidade etc.)…”
Section: Discussionunclassified

Desmistificação De Mitos Botânicos Por Meio Do Estudo Da Fisiologia De Plantas

Heloisa de Medeiros Camargo,
Julia de Medeiros Camargo,
Mesquita de Oliveira
et al. 2024
RECIMA21